2016
DOI: 10.1016/j.jid.2016.02.809
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Roles of Polycomb Repressive Complex 2 Subunits in the Control of Skin Development

Abstract: Polycomb repressive complex 2 (PRC2) is an essential regulator of cell physiology. While there have been numerous studies on PRC2 function in somatic tissue development and stem cell control, these have focused on the loss of a single PRC2 subunit. Recent studies, however, have shown that PRC2 subunits may function independently of the PRC2 complex. To investigate the function of PRC2 in the control of skin development, we generated and analysed three conditional knockout mouse lines, in which the essential PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 41 publications
(76 reference statements)
3
56
2
Order By: Relevance
“…Using quantitative‐ChIP experiments, wound‐induced genes Myc and EGFR were found de‐repressed by loss of H3K27me3 and EED occupancy . These data correlated with PRC2 complex gene ablation studies where epidermal hyperproliferation was observed, which could explain how BL cells lose H3K27me3 marks during wound repair . Also, Ezh1/2 double‐knockout split‐thickness engraftment demonstrated delayed re‐epithelization from the HF after wounding, suggesting that knockout bulge‐SCs have less re‐epithelization potential .…”
Section: Epigenetic Reprogramming During Injury‐induced Epidermis Regsupporting
confidence: 57%
See 2 more Smart Citations
“…Using quantitative‐ChIP experiments, wound‐induced genes Myc and EGFR were found de‐repressed by loss of H3K27me3 and EED occupancy . These data correlated with PRC2 complex gene ablation studies where epidermal hyperproliferation was observed, which could explain how BL cells lose H3K27me3 marks during wound repair . Also, Ezh1/2 double‐knockout split‐thickness engraftment demonstrated delayed re‐epithelization from the HF after wounding, suggesting that knockout bulge‐SCs have less re‐epithelization potential .…”
Section: Epigenetic Reprogramming During Injury‐induced Epidermis Regsupporting
confidence: 57%
“…Specifically, loss of Ezh1/2 resulted in hyperproliferative IFE, whereas the follicular region showed proliferative arrest. Similarly, loss of other PRC2 components, Eed and Suz12, showed IFE hyperproliferation and HFs morphogenesis arrests due to proliferation defects and increased apoptosis . In addition, loss of these PRC2 genes showed an ectopic formation of Merkel cells in the epidermis, which are essential for sensory function of the skin by activation of the Merkel cell‐specific genes, Isl1 and Sox2 .…”
Section: Histone Methylation In Skin Development and Homeostasismentioning
confidence: 98%
See 1 more Smart Citation
“…However, in the glabrous paw skin, loss of Shh or Smo had much less of an effect on Merkel cell formation as these cells were still formed, and their total count was only slightly reduced, compared to control (Table ). This lesser effect on Merkel cell formation was also found in the glabrous paw skin when coupling the loss of Smo with the loss of EED , a component of the Polycomb repressive complex (PRC) 2 that temporally restricts Merkel cell formation . Loss of EED leads to an ectopic expansion of Merkel cells in both the back and glabrous paw skin .…”
Section: Resultsmentioning
confidence: 84%
“…This lesser effect on Merkel cell formation was also found in the glabrous paw skin when coupling the loss of Smo with the loss of EED , a component of the Polycomb repressive complex (PRC) 2 that temporally restricts Merkel cell formation . Loss of EED leads to an ectopic expansion of Merkel cells in both the back and glabrous paw skin . Concurrent loss of EED and Smo in the skin epithelium depleted Merkel cells in the back skin; however, it leads to a slight increase in the number of Merkel cells in the glabrous paw skin (Table ).…”
Section: Resultsmentioning
confidence: 86%